Medi(a)tion - Rodrigues, Iasmim Dala Bernardina; Fernandes, João Victor Silva (Revista do Colóquio, 2024)
The premise of this report was to understand how the art mediator’s perception can influence the observer’s understanding and how, based on this interaction with the visitor, it helps, in theory, to be a two-way street; since the mediator can also be influenced by the way in which the public receives and interprets the works presented. To this end, it was initially chosen to work with the soliloquy. In the soliloquy, the mediator expresses his understanding of the artists, creating questions and answering them immediately. Next, it was necessary to describe how this quid pro quo works in practice, bringing the mediator’s questions to the public, to finally end with the consequences generated by this dialogue.